Tree performance in a biodiversity enrichment experiment in an oil palm landscape - Zemp, Clara; Anne Gérard; Dirk Hölscher; Christian Ammer; Bambang Irawan; Leti Sundawati; Miriam Teuscher; Holger Kreft (My University, 2019)
1. Large‐scale conversion of tropical forests into oil palm monocultures has led to dramatic losses of biodiversity and ecosystem functions. While ecological restoration is urgently needed in many oil palm landscapes, there is a lack of scientific knowledge of sustainable management strategies. 2. We established experimental tree islands of varying sizes (25 m2 to 1,600 m2) and diversity levels (1, 2, 3 and 6 species) in an oil palm plantation in Sumatra, Indonesia. Six native multi‐purpose tree species including Archidendron pauciflorum (Jengkol), Durio zibethinus (Durian), Parkia speciosa (Petai), Shorea leprosula (Meranti), Peronema canescens (Sungkai) and Dyera polyphylla (Jelutung) were planted between living and felled oil palms. Here, we analyse the controlling factors of tree growth and survival during the first 4 years at the level of local neighbourhood and tree island. 3. We found a significant effect of diversity levels on tree productivity, that is, basal area was higher in multi‐species than in single‐species tree islands. This overyielding was attributed to enhanced tree growth, while mortality had no effect. In the local neighbourhood, tree species richness had a positive effect on tree growth during the first year only, indicating that selection and dominance of well‐performing species at high level of diversity are most likely driving overyielding. 4. Trees grew better away from living oil palms, suggesting tree‐palm competition. Proximity to felled oil palms increased growth especially during the first years, during which the planted trees might have benefited from the additional available space and resources. Despite positive edge effects from the conventional oil palm management in the surrounding, tree island size had an overall positive effect on tree growth. 5. Synthesis and applications. We planted native trees in an oil palm landscape following a tree island pattern. The establishment success differed widely among the six planted species. The selection of particular species is a decisive factor to foster a positive relationship between diversity and tree growth. Planting larger tree islands (e.g. 1,600 square metres) is a better option to enhance tree growth, but tree‐palm competition implies a trade‐off between tree growth and palm oil production in the tree islands.
Keywords: agroforestry; diversity‐productivity relationship; forest landscape restoration; Indonesia; sustainable oil palm; tree diversity experiment; tree growth; tree islands; TreeDivNet